2021
DOI: 10.1108/bepam-02-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

A curriculum guide model to the next normal in developing construction supervisory training programmes

Abstract: PurposeThis study aims to develop a curriculum guide model to upgrade the construction supervision practices, considering evolving challenges and thereby the next normal of the industry.Design/methodology/approachBoth qualitative and quantitative research designs were adopted to identify productivity-related challenges that can be addressed through effective supervision in construction. Meetings, discussions, workshops and surveys were conducted among construction experts to systematically develop the competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(164 citation statements)
references
References 14 publications
(33 reference statements)
0
73
0
Order By: Relevance
“…The problem-based communication approaches were mainly used in the discussion sessions, and the results were validated through these discussion outcomes. The problem-based communication approaches are very useful for understanding the issues, exchanging information, generating ideas and finding solutions (Manoharan et al. , 2021a).…”
Section: Methodsmentioning
confidence: 99%
“…The problem-based communication approaches were mainly used in the discussion sessions, and the results were validated through these discussion outcomes. The problem-based communication approaches are very useful for understanding the issues, exchanging information, generating ideas and finding solutions (Manoharan et al. , 2021a).…”
Section: Methodsmentioning
confidence: 99%
“…Though several studies reported the significant factors that affect the labour performance in construction, only a few focused on the track of labour training development towards labour performance improvement (Siregar, 2018;Gao et al, 2019;Ojha et al, 2020;Manoharan et al, 2021b). Ojha et al (2020) have reviewed the training methods and evaluation techniques to measure the effectiveness of construction labourers in health and safety practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies also spotlight the need for improving training facilities for construction supervisors in many countries [4,5,15,24], including Sri Lanka [25][26]. Supervision practices act as a vital link between the management and labour, and these are significant to improve the performance and productivity of labour operations in construction [15,24,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incompetent supervisors, supervisor absenteeism and poor resource management skills had been the major problems for the Indonesian contractors [6]. Though no recent studies reported the supervisor absenteeism as a significant factor, their inefficient site management and poor site coordination skills have been the significant factors affecting the progress of construction projects in many countries' recent scenarios [12,[22][23][24]26]. This confirms that the transferable skills of construction supervisors must be further addressed in the construction supervisory training programmes in many countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation